How parents habitualize prayer in their adolescent children: Developing an optimal model through grounded theory approach - somayeh Gholami; Mokhtar Zakeri; Fatemeh Zeinali (مسائل کاربردی تعلیم و تربیت اسلامی, 2019)
The purpose of the present study is to investigate  the ways to strengthen and deepen praying culture in children. This is a qualitative research, on the basis of grounded theory method. The participants include 25 parents of a high school second grade students in Bander Lengeh. The selected parents were successful in educating their children to adhere to praying. The data were collected through semi-structured deep interview. Data analysis was carried out through three stages of open, pivotal and selective coding. Finally, a model was presented regarding conditions, grounds, and strategy. Validity of the study was provided by a non-member inspector and was evaluated by the members. The results of the final model indicated that parents should have a strong dedication to the religious development of their children in order to accustom them to ritual prayer. This general condition includes underlying factors such as creating a religious attitude in life, modeling, belief-behavior consistency, and promotion of personal growth. Strategies that parents can use are functions that they perform in the pre-birth age, pre-maturity age, maturity age, and post-maturity age of  their child(ren). The effective parenting measures in order to control the interfering variables in the training path are adoption of positive and effective parenting style, using problem solving skills and environment immunization. In general, childrenchr('39')s adherence to praying does not accidentally and requires careful planning, study, and parental follow-up from pre-birth age of their offspring.